Barriers to Local Community Involvement in Community-Based Tourism Development: Evidence from Area Model of Conservation and Education (AMCE) Oro-Oro Ombo Village Batu City Indonesia - Rahman, Fathur; Made Kutanegara, Pande; Bachruddin, Zaenal; Susilastuti, Dewi Haryani (Politeknik Negeri Bandung, 2024)
Local community involvement plays a critical role in the success of tourism development, particularly in community-based tourism (CBT). This study investigates the internal barriers to local community involvement in the Area Model Conservation and Education (AMCE), a CBT destination in Oro-Oro Ombo Village, Batu City, Indonesia. Using purposive and snowball sampling techniques, data were collected from informants, including tourism destination managers, village government employees, Village Consultative Body (VCB) members, and local community leaders. Data collection methods comprised in-depth interviews, participant observation, and documentation, which were subsequently analyzed through content analysis. The findings reveal five categories of tourism development in AMCE, including economic, social, environmental, geographical, and institutional. The dominant inhibitors come from the institutional category, such as top-down leadership style, less transparent governance, internal conflicts between managers, and elite capture in AMCE. These barriers hinder effective community participation and sustainable tourism development in the region. The study emphasizes the need for enhanced organizational governance, better financial resource allocation, and improved coordination and collaboration with government agencies, universities, and other stakeholders. Additionally, capacity-building initiatives, including education and training programs for tourism destination managers, are essential to overcoming these barriers. The results provide critical insights for policymakers and practitioners to foster inclusive and sustainable tourism development in CBT destinations.